Mesangial cell: A hub in lupus nephritis - Liu, Mengdi; Zhang, Lei; Wang, Yixin; Hu, Weijie; Wang, Chunhong; Wen, Zhenke (Frontiers in Immunology, 2022)
Lupus nephritis (LN) is a severe renal disease caused by the massive deposition of the immune complexes (ICs) in renal tissue, acting as one of the significant organ manifestations of systemic lupus erythematosus (SLE) and a substantial cause of death in clinical patients. As mesangium is one of the primary sites for IC deposition, mesangial cells (MCs) constantly undergo severe damage, resulting in excessive proliferation and increased extracellular matrix (ECM) production. In addition to playing a role in organizational structure, MCs are closely related to in situ immunomodulation by phagocytosis, antigen-presenting function, and inflammatory effects, aberrantly participating in the tissue-resident immune responses and leading to immune-mediated renal lesions. Notably, such renal-resident immune responses drive a second wave of MC damage, accelerating the development of LN. This review summarized the damage mechanisms and the in situ immune regulation of MCs in LN, facilitating the current drug research for exploring clinical treatment strategies.